Adenocarcinoma insitu presenting as extensive crazy paving pattern: HRCT findings and review of literature - Rahul Dev; Pankaj Sharma; Yasrab Khan (International Journal of Medical Research and Review, 2018)
The crazy-paving pattern seen on HRCT is comprised of diffuse areas of ground glass attenuation. This imaging finding has numerous differentials including idiopathic, infectious, neoplastic and other miscellaneous entities. A 52-year-old non-smoker presented with mild to moderate dyspnoea with occasional cough and restrictive pattern on PFT. Chest radiograph showed bilateral diffuse air space opacities with crazy paving pattern on High resolution CT of the lung. This pattern has numerous differentials with pattern of lung involvement, the patient’s history and clinical findings being helpful in narrowing the diagnosis.